Treating infants’ colic - Rogovik, Alex L. (College of Family Physicians of Canada, 2005)
QUESTION: Young parents often visit my office because their infants are crying inconsolably. Results of physical examination are unremarkable, so colic is the most likely cause. Colic has been known for many years, but I am unaware of any good remedy for it. Are there any modern, effective, safe methods of managing colic? ANSWER: In most cases, colic is a “noisy phenomenon” for which there is no good explanation or treatment. Changing babies’ feedings rarely helps, and effective pharmacologic remedies are as yet unavailable. Several behavioural and complementary therapies have been suggested, but they have not been found effective. Addressing parental concerns and explaining about colic is the best solution until the colic goes away.